OPTIMIZING WILLINGNESS TO PAY FOR THE PRESERVATION OF SIBOLANGIT NATURE PARK IN NORTH SUMATERA - Febri Yoanita Harahap; Delvian, Isnen Fitri (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Nature Tourism Park (TWA) is a conservation area that is formed and aims to be used as a location for tourism, education, research and cultural preservation. By looking at the completeness of the facilities and the potential of the flora and fauna in Sibolangit TWA, it should have the potential to be visited by more tourists. Moreover, its location is only 38 km from Medan City or one hour by road using a motorized vehicle, the place is on the edge of the Medan - Berastagi crossing road. The decline in visitors over the past 2 years has had an impact on the low income received by TWA Sibolangit, which is also one of the sources of PNBP (Non-Tax State Revenue). This study was conducted to answer several research questions, including: 1) What are the factors that affect WTP in Sibolangit TWA? Logistic regression analysis was used and 2) How much is the WTP value by visitors to Sibolangit TWA? Using CVM and average WTP. The target of the questionnaire is teenage visitors (12-25 years old). From the results of the study it is known that the significance value of each variable is smaller than 5 percent of only three variables, namely the variable gender, level of knowledge, and visitor perceptions of service. And based on the above calculations, the average WTP value of respondents is idr. 7,875. Rounded up to idr. 8,000,-